Long non-coding RNA XIST promotes the progression of esophageal squamous cell carcinoma through sponging miR-129-5p and upregulating CCND1 expression. Issue 1 (2nd January 2021) - Wang, Haoran; Li, Haomiao; Yu, Yongkui; Jiang, Qingfeng; Zhang, Ruixiang; Sun, Haibo; Xing, Wenqun; Li, Yin
ABSTRACT: Long non-coding RNA (lncRNA) X inactive specific transcript (XIST) has been identified as an oncogenic lncRNA in a series of human cancers, including esophageal squamous cell carcinoma (ESCC). In this study, we aimed to further explore the underlying mechanism of XIST on ESCC progression. qRT-PCR assay was used to determine the levels of XIST and miR-129-5p. Western blot analysis was performed to assess cyclin D1 (CCND1) expression. Bioinformatic analysis was performed using starBase v2.0 software. Dual-luciferase reporter and RNA immunoprecipitation assays were employed to confirm the interaction between XIST and miR-129-5p or miR-129-5p and CCND1. Cell cycle progression and apoptosis were measured by flow cytometric analysis, and cell migration and invasion were detected by transwell assay. Mouse studies were used to observe the effect of XIST silencing on tumor growth in vivo . Our results indicated that XIST was upregulated and miR-129-5p was downregulated in ESCC. XIST silencing or miR-129-5p overexpression repressed cell cycle progression, proliferation, migration, invasion, and promoted the apoptosis in ESCC cells. Moreover, XIST directly interacted with miR-129-5p and repressed miR-129-5p expression. MiR-129-5p mediated the regulatory effect of XIST on ESCC cell progression in vitro, and XIST promoted CCND1 expression by sponging miR-129-5p. Additionally, XIST silencing inhibited tumor growth in vivo . Our findings suggested that XIST silencing repressed the progression of ESCC at least partly through regulating the miR-129-5p/CCND1 axis. Targeting XIST might be a potential therapeutic strategy for ESCC treatment.